Dosis de gallinaza y su efecto en las características agronómicas y rendimiento de forraje de Moringa oleífera "moringa" en Zungarococha - 2021 - Valles Grandez, Carlos Martin (2022)
Currently there are crops that can serve for human health and also for animal feed, the National University of the Peruvian Amazon through the Faculty of Agronomy carried out this research work entitled DOSIS OF CHICKEN MANURE AND ITS EFFECT ON THE AGRONOMIC CHARACTERISTICS AND FORAGE YIELD OF Moringa oleifera "MORINGA" IN ZUNGAROCOCHA - 2021. The evaluations were carried out 60 days after the start of the research work, with plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2. With a Complete Randomized Block Design (D.C.A), with five treatments and four repetitions, the treatments under study were: T0 (Control), T1 (10 tons of chicken manure/ha), T2 (20 tons of chicken manure/ha), T3 (30 tons of chicken manure/ha), obtaining the following results: With treatment T4 (40 tons of chicken manure/ha), having the following response of the moringa crop of an increase in plant height of 1.90 m., yields of green matter (kg/m2) and dry matter (kg/m2) of 2.06 kg/m2 and 0.43 kg/m2, with the leaf/stem ratio being 0.57 kg. with a plant cover of 90.45% and a yield of kilos per hectare of green matter of 20,600 kg/ha. According to what was found in this work, the dose of 40 tons of chicken manure per hectare of chicken manure positively influences the investigation.